Treatment of acetaminophen and acetylsalicylic acid by chicken bone based adsorbent - Nurshuhada Amira Yusoff, 1992-, author 625433 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Thesis (Sarjana Falsafah) - Universiti Teknologi Malaysia, 2019